An Implementation Islamic Education Model to Build Tolerance and Prevent Radicalism at An Islamic Boarding School - Fauziah, Debibik Nabilatul; Ramdhani, Khalid; Muzaki, Iqbal Amar; Permana, Inggil; bin Ellias, Mohd Sobri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study is motivated by increasing reports of intolerance and radicalism that often involve individuals with religious educational backgrounds, even though Islamic teachings fundamentally reject all forms of violence and terrorism. Islamic Religious Education (PAI) is therefore expected to play a central role in shaping moderate, tolerant, and peace-loving attitudes among students, particularly within Islamic boarding schools (pesantren), which are known for their strong religious traditions and moral education. The aim of this study is to develop PAI teaching materials in Islamic boarding schools that emphasize tolerance values and the prevention of radicalism. The research was conducted at Al Istiqomah Boarding School, Sindangsari, Kutawaluya, Karawang, using a qualitative descriptive approach with a case study design. The main participants were students, teachers, and Kyai. Data were obtained through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the values of tolerance at Al Istiqomah Boarding School are internalized through PAI learning, teachers’ exemplary conduct, and religious activities that foster respect, cooperation, and appreciation for diversity. The study concludes that pesantren have a strategic role in strengthening character education based on tolerance and preventing the spread of radical ideologies among students.